(untitled) (Journal of the College of Basic Education, 2022)
This study attempts to explore the common syntactic errors in the English writing made by students of secondary schools in Iraq. The corpus of the study consisted of 97 students at the fourth grade at A-Siraj secondary school for boys in Baghdad (2015- 2016). The study uses Error Analysis to identify, describe, and classify errors and to determine their causes. It also uses the Contrastive Analysis as a method of describing the structural systems of Arabic and English. The study investigated the exam essays written by the students and the results show that verb group errors were found to be the largest group in number. The next largest groups of errors occurred consecutively in: tense, prepositions, articles, word order and voice. The study concluded that interference from the mother tongue, faulty assumptions about the target language and inconsistency of English constitute the main sources of errors. Finally, some pedagogical recommendations are presented for English teachers and syllabus designers